The COVID-19 Mask: Toward an Understanding of Social Meanings and Responses. (18th October 2021) - St-Amant, Oona; Rummens, J. Anneke; Parada, Henry; Wilson-Mitchell, Karline
Abstract : The COVID-19 pandemic has imposed unprecedented restrictions on everyday life. Unlike lockdown or shelter-in-place measures, the facemask has emerged as an empowering response to the public spread of the virus, permitting some degree of return to prepandemic life—such as school or work—by disrupting transmission that would otherwise occur. And yet, this utilitarian tool has attracted considerable controversy and polarized opinions. This article uses Blumer's adaptation of symbolic interactionism as a theoretical roadmap to examine the various meanings ascribed to the facemask and its usage. We discuss how it is socially perceived and consider implications for health care providers within the Canadian social context.